Environmental Degradation and Poverty Nexus: Evidence from Coral Reef Destruction in Indonesia - Kanetasya Sabilla (Journal of Indonesian Social Sciences and Humanities, 2017)
In a rural area, environmental degradation and poverty nexus focuses on the high-dependency of poor people to natural resources-based livelihood. Arguably, limited assets of poor people cause them to be unable to cope with natural resources degradation and to undertake sustainable practice in their livelihood activities. This study attempts to find the nexus between environmental degradation and poverty in the case of coral reef destruction in Indonesia by applying secondary research as a methodology. A sustainable livelihood framework is applied to analyze small-scale fisher people's vulnerability and capacity to destruct. This study finds that small-scale fisher-people have limited assets to cope with coral reef destruction; however, the same condition leads them to destruct coral reef by doing the destructive fishing practice. This condition causes them to be trapped in the downward spiral of environmental degradation and poverty. Moreover, small-scale fisher-people can overcome this problem by developing self-governance common pool resources to conserve coral reef and increase their livelihood sustainability.